pengaruh sistem akuntansi manajemen dan teknologi informasi terhadap kinerja operasional: sistem akuntansi manajemen - Wita, Purwita (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
Operational performance is the suitability of processes and performance evaluation of the company’s internal operations starting from the perspective of costs, customer service, quality, flexibility and process quality of goods and services. This research aimsl to determinel and analyzel the influence ofl management accountingl systems andl information technology on operational performancel at lPT. Astra International Tbk Medan Branch Gatot Subroto. Thel results showl that managementl accounting systemsl and information technology have a significant effectl on operational lperformance. The variable managementl accounting systeml and informationl technology onl operational performance is known to have a valuel of lFcount > Ftable, namely 104.853 > l3.20 andl a significantl value ofl 0.000 < l0.05. This means thatl the managementl accounting systeml and information technology variables havel a significanlt effect onl operational performance. The results of thel analysis above certainly influence operational performance because management accounting systems andl information technologyl are one ofl the factorsl that influencel operational performance.